PENERAPAN PEMBELAJARAN PROBLEM BASED LEARNING TIPE SSCS UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Nina Erlina (Edutainment, 2019)
This research discusses the application of the SSCS type problem based learning model to improve student learning outcomes in class X1 AK1 SMKN 1 Sungailiat. The research method used in this study is PTK that is done with the type of search, solve, create, and share (SCSS) in the subject of Accounting material about closing journal. The findings show: 1) the SSCS type problem based learning model can improve student learning outcomes, this can be proven by comparing the test scores in each cycle. 2) this learning model is also able to overcome miss-matches, especially on social concepts that are abstract and require real evidence from real life to brought into the learning process. 3) obstacles encountered related to the application of this learning method namely: a) the teacher involved was not accustomed to using PBL learning models with this type of SSCS before, so that it had a little difficulty in applying it. After several meetings, the teacher is accustomed to adapt in optimizing their use for learning activities of students in the classroom. b) students want the learning phase and the experiments they do are designed to be more interesting and interactive, and contain examples of real activities that are more related to the material discussed.